THE LONG ROAD TO DEATH: NOTES ON PRE AND POST BURIAL TREATMENTS IN CONTEMPORARY CEMETERY FROM PERU - Estrada Moreno, Flavio (2013)
We present a series of field notes made during the recovery efforts of human remains and associated elements of people killed mostly during the 80s to 2000 in various cemeteries of Peru.